1971
DOI: 10.1051/jphyscol:1971438
|View full text |Cite
|
Sign up to set email alerts
|

Polarisation Des Spectres Caractéristiques d'ÉMISSION X Et Étude De La Structure Électronique Des Corps Solides

Abstract: Pas de Résumé disponibl

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1978
1978
2003
2003

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Therefore, a t first it was looked for a polarization effect in the valence band spectrum of graphite. After Borovskii et al [9] had found first indications of an anisotropy of the CK emission of graphite by using lead stearate as monochromator the effect was proved unambiguously by Brummer et al [lo]. With a graphite sample cut parallel to the c-axis and mounted in a concave grating spectrometer with the sample orientations A and B as shown in Fig.…”
Section: Polarized Valence Band Spectra Of Layer Crystalsmentioning
confidence: 95%
“…Therefore, a t first it was looked for a polarization effect in the valence band spectrum of graphite. After Borovskii et al [9] had found first indications of an anisotropy of the CK emission of graphite by using lead stearate as monochromator the effect was proved unambiguously by Brummer et al [lo]. With a graphite sample cut parallel to the c-axis and mounted in a concave grating spectrometer with the sample orientations A and B as shown in Fig.…”
Section: Polarized Valence Band Spectra Of Layer Crystalsmentioning
confidence: 95%